2018
DOI: 10.11144/javeriana.umed60-1.cand
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Candidemia at a University Hospital in Colombia, 2008-2014

Abstract: Introduction: Candida species are commensal yeasts of the human microbiota. However, due to several host’s conditions, bloodstream infections may arise causing high morbimortality. Methods: Retrospective cross-sectional analytical study of positive blood cultures for Candida spp. between 2008-2014 at a university hospital in Bogota, Colombia. We evaluated clinical and microbiological characteristics prior to the first positive blood sample was obtained and determined associations with non-C. albicans (NCA) spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 56 publications
(67 reference statements)
0
4
1
Order By: Relevance
“…However, the percentage of C. tropicalis (26.8% vs. 13.6%) and C. parapsilosis (19.5% vs. 13.6%) found differs from that observed in the first decade of the 2000s in Colombia [36]. Similar results were found for species distribution in studies conducted at the same hospital between 2003 and 2014, however, we observed a slight increase in NACS (62 ,6% vs. 58%) and the presence of C. auris, which was not described in these studies [37,38]. In the region, a study that evaluated susceptibility of the species identified in Colombia, Ecuador, and Venezuela, found a percentage of resistance to FLC of 6.8% [39].…”
Section: Discussioncontrasting
confidence: 51%
“…However, the percentage of C. tropicalis (26.8% vs. 13.6%) and C. parapsilosis (19.5% vs. 13.6%) found differs from that observed in the first decade of the 2000s in Colombia [36]. Similar results were found for species distribution in studies conducted at the same hospital between 2003 and 2014, however, we observed a slight increase in NACS (62 ,6% vs. 58%) and the presence of C. auris, which was not described in these studies [37,38]. In the region, a study that evaluated susceptibility of the species identified in Colombia, Ecuador, and Venezuela, found a percentage of resistance to FLC of 6.8% [39].…”
Section: Discussioncontrasting
confidence: 51%
“…Studies have shown that C. albicans is the most common fungi species of Vulvovaginal Candidiasis (VVC), Candidemia, and invasive Candida infections (IC). [1][2][3] The five major antifungal agents used in the treatment of C. albicans infection are azoles, allylamines, echinocandins, polyenes and nucleoside analogues. According to a Japanese study, the trend of antifungal drugs use for invasive mycoses increased between 2006 and 2015.…”
Section: Introductionmentioning
confidence: 99%
“…(14,32) The most prevalent species in the present study and most other studies was C. albicans, with it being responsible for approximately 50% of all infections; however, C. glabrata, C. tropicalis, C. parapsilosis, and C. krusei are also important infectious agents. (6,(33)(34)(35)(36)(37)(38)(39) The present study identified C. dubliniensis in 8.5% of patients using a species-specific PCR to differentiate this species from C. albicans. Chavasco et al (29) identified C. dubliniensis in 5.4% of patients using PCR, in which samples had been mistakenly identified as C. albicans by the classical method, thus demonstrating that PCR is more effective in elucidating the epidemiology of C. dubliniensis and establishing its clinical significance.…”
Section: ❚ Discussionmentioning
confidence: 89%
“…albicans, with it being responsible for approximately 50% of all infections; however, C. glabrata , C. tropicalis , C. parapsilosis , and C. krusei are also important infectious agents. ( 6 , 33 - 39 )…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation